Use of Guideline-Based Therapy for Diabetes, Coronary Artery Disease, and Chronic Kidney Disease After Acute Kidney Injury: A Retrospective Observational Study. (June 2022) - Madan, Sunchit; Norman, Patrick A.; Wald, Ron; Neyra, Javier A.; Meraz-Muñoz, Alejandro; Harel, Ziv; Silver, Samuel A.
Background: Survivors of acute kidney injury (AKI) are at a high risk for cardiovascular complications. An underrecognition of this risk may contribute to the low utilization of relevant guideline-based therapies in this population. Objective: We sought to assess accordance with guideline-based recommendations for survivors of AKI with diabetes, coronary artery disease (CAD), and preexisting chronic kidney disease (CKD) in a post-AKI clinic, and identify factors that may be associated with guideline accordance. Design: Retrospective cohort study. Setting: Post-AKI clinics at 2 tertiary care centers in Ontario, Canada. Patients: We included adult patients seen in both post-AKI clinics between 2013 and 2019 who had at least 2 clinic visits within 24 months of an index AKI hospitalization. Measurements: We assessed accordance to recommendations from the most recent North American and international guidelines available at the time of study completion for diabetes, CAD, and CKD. Methods: We compared guideline accordance between visits using the Cochran Mantel Haenszel test. We used multivariable Poisson regression to identify prespecified factors associated with accordance. Results: Of 213 eligible patients, 192 (90%) had Kidney Disease Improving Global Outcomes Stage 2-3 AKI, 91 (43%) had diabetes, 76 (36%) had CAD, and 88 (41%) had preexisting CKD. From the first clinic visit to the second, there was an increase in angiotensin-converting enzyme inhibitor/angiotensin receptor blocker (ACE-I/ARB) use across all disease groups—from 33% to 46% ( P = .028) in patients with diabetes, from 30% to 57% ( P = .002) in patients with CAD, and from 16% to 35% ( P < .001) in patients with preexisting CKD. Statin use increased in patients with preexisting CKD from 64% to 71% ( P = .034). Every 25 μmol/L rise in the discharge serum creatinine was associated with a 19% (95% confidence interval [CI], 8%-28%) and 12% (95% CI, 2%-21%) lower likelihood of being on an ACE-I/ARB in patients with diabetes and preexisting CKD, respectively. Limitations: The study lacked a comparison group that received usual care. The small sample and multiple comparisons make false positives possible. Conclusion: There is room to improve guideline-based cardiovascular risk factor management in survivors of AKI, particularly ACE-I/ARB use in patients with an elevated discharge serum creatinine.